NATURAL AND GEOGRAPHICAL CONDITIONS OF THE YAZYAVAN DISTRICT (Scientific journal of the Fergana State University, 2025)
The article describes the geographical location of the Yazyavan district, climatic, geological-geomorphological, hydrogeological and hydrological conditions, as well as some properties of its soils.